FLEET ASSIGNMENT MODELLING - L. V. Pavlova (Научный вестник МГТУ ГА, 2016)
The article is devoted to the airline scheduling process and methods of its modeling. This article describes the main stages of airline scheduling process (scheduling, fleet assignment, revenue management, operations), their features and interactions. The main part of scheduling process is fleet assignment. The optimal solution of the fleet assignment problem enables airlines to increase their incomes up to 3 % due to quality improving of connections and execution of the planned number of flights operated by less number of aircraft than usual or planned earlier. Fleet assignment of scheduling process is examined and Conventional Leg-Based Fleet Assignment Model is analyzed. Finally strong and weak aspects of the model (SWOT) are released and applied. The article gives a critical analysis of FAM model, with the purpose of identifying possible options and constraints of its use (for example, in cases of short-term and long-term planning, changing the schedule or replacing the aircraft), as well as possible ways to improve the model.